Inkuiri Terbimbing Berbasis Blended Learning: Memperkuat Keterampilan Proses Sains Melalui Pembelajaran Koloid - Iriani Bakti; Reni Hafizah; Arif Sholahuddin (Postgraduate, University of Mataram, 2023)
Science process skills play a crucial role in constructing knowledge and fostering the ability to independently solve problems. Despite their significance, the science process skills of students across various educational levels remain at a relatively low level. This research seeks to evaluate the science process skills of students and their responses to learning about colloids through a blended learning-based guided inquiry approach. The research employs a quasi-experimental design with a pretest-posttest control group setup. The sample, drawn through cluster random sampling, consists of students from Class XI MIPA 1 at SMAN 11 Banjarmasin, divided into two groups. Group A, the experimental class, engages in blended learning-based guided inquiry, while Group B, the control class, follows the guided inquiry model. Data collection involves tests to assess students' science process skills and non-tests to gauge their responses. The analysis entails descriptive techniques and t-tests. The findings indicate (1) discernible differences in science process skills between classes employing blended learning-based guided inquiry and guided inquiry alone, and (2) a positive response from students towards the blended learning-based inquiry model.